Trade Facilitation and Agriculture Sector Performance in Sub-Saharan Africa: Insightful Policy Implications for Economic Sustainability - Ibrahim, Ridwan Lanre; Yu, Zhang; Hassan, Shafiqul; Ajide, Kazeem Bello; Tanveer, Muhammad; Khan, Abdul Rehman (Frontiers in Environmental Science, 2022)
This study investigates the impact of trade facilitation though costs, documents, and time to import and export – on agricultural sector performance (ASP) for a panel of 33 Sub-Saharan African (SSA) countries from 2005 to 2019. The empirical analysis is based on a dynamic system of generalized method of moments. The following findings are established. First, higher import costs, documents, and time significantly improve ASP, while exports negatively impact ASP. Second, while import costs promote trade in agricultural products through substitution effects, export costs impede it. Third, among other factors, improvements in human capital, gross fixed capital formation, population growth, and trade openness significantly improve agricultural sector performance. Fourth, the results of the robustness check further emphasize the importance of TF on ASP from various dimensions. The study concludes that improving TF procedures by reducing costs, documents, and time in cross-border trade remains crucial to boosting agriculture sector performance in SSA.